The multicentroid position of the anthropomorphological profile of female volleyball players at different competitive levels - Dopsaj, M.; Nesic, G.; Copic, N. (Facta Universitatis: Series Physical Education and Sport, 2010)
The aim of the paper was to determine which anthropomorphological (AM) features are possessed by players who competed at the elite international level (Olympic Games), at the elite national level (Super League) and the federal level (second division - North) in order to classify the most important AM characteristics that determine competitive performance in volleyball for women. A set of 11 variables, measured by standardized tests in field measurement conditions, was used for the assessment of their anthropomorphological profiles. The data were processed by a multivariate statistical method. The results showed that there is a general statistically significant difference in the AM profiles between female volleyball players of different competitive levels (Wilks' Lambda Value-0156, F=4927, 0000 and p=0.000) mostly in body height, LBM, body weight and upper leg skin folds. In terms of selection and in function of AM space, the top female volleyball players must be of above-average height and with morphological features which provide them with an outstanding speed-explosive motor potential.